2017
DOI: 10.1007/s00018-017-2695-6
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of p53 drives autophagy during human trophoblast differentiation

Abstract: The placental barrier is crucial for the supply of nutrients and oxygen to the developing fetus and is maintained by differentiation and fusion of mononucleated cytotrophoblasts into the syncytiotrophoblast, a process only partially understood. Here transcriptome and pathway analyses during differentiation and fusion of cultured trophoblasts yielded p53 signaling as negative upstream regulator and indicated an upregulation of autophagy-related genes. We further showed p53 mRNA and protein levels decreased duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…To obtain a global view on functional changes during villous trophoblast differentiation, we analyzed the biological processes enriched among differentially expressed genes by DAVID (Table S4) and visualized their network by using the BiNGO [98] plugin in Cytoscape. As a good confirmation of our analysis, many of the most enriched biological processes ( Figure 3a) have been delineated by earlier studies on villous trophoblast differentiation [5,6,99]. There is a wide range of enriched biological processes (n = 952) related to the morphological and functional transformation from a proliferative cytotrophoblast into a metabolically and hormonally active end-differentiated syncytiotrophoblast, including 'programmed cell death', 'tissue development', 'apoptotic process', and 'cell cycle' as top enriched GO biological processes among differentially expressed (DE) genes (Table S4).…”
Section: Microarray Analysis Reveals Global Transcriptomic and Functisupporting
confidence: 87%
“…To obtain a global view on functional changes during villous trophoblast differentiation, we analyzed the biological processes enriched among differentially expressed genes by DAVID (Table S4) and visualized their network by using the BiNGO [98] plugin in Cytoscape. As a good confirmation of our analysis, many of the most enriched biological processes ( Figure 3a) have been delineated by earlier studies on villous trophoblast differentiation [5,6,99]. There is a wide range of enriched biological processes (n = 952) related to the morphological and functional transformation from a proliferative cytotrophoblast into a metabolically and hormonally active end-differentiated syncytiotrophoblast, including 'programmed cell death', 'tissue development', 'apoptotic process', and 'cell cycle' as top enriched GO biological processes among differentially expressed (DE) genes (Table S4).…”
Section: Microarray Analysis Reveals Global Transcriptomic and Functisupporting
confidence: 87%
“…BRCA1 immunostaining within the ST was weaker and restricted to a few nuclei. A similar distribution pattern, i.e., absence or weak expression in ST versus high expression on vCTs and EVTs, has been described for several other cell cycle regulators including Ki67, cyclin A, p53, and p57 [24,43]. Considering that ST is characterized by the absence of an active cell cycle [44], BRCA1 positive nuclei within the ST might be the result of recent vCT-ST fusion.…”
Section: Discussionsupporting
confidence: 61%
“…However, a simplistic view on the association between p53 levels and autophagy was challenged by the notion that even more autophagy was detected concomitant with reduced levels of p53 when the BCP-ALL cells were co-exposed to irradiation and activators of the cAMP signaling pathway. Although reports have suggested that lowering the levels of p53 may facilitate autophagy [ 42 , 43 ], the consensus has been that the subcellular localization of p53 dictates its role in autophagy. Thus, induction of nuclear p53 is assumed to promote autophagy, whereas p53 in the cytosol protects the cells from autophagy [ 20 , 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%